Anifungi Activity Test of Ethanoled Extract of Cashew Gua Leaves (Anacardium occidentale) Against Candida albicans - Yunita, Yunita; Hidayati, Agriana Rosmalina; Hajrin, Wahida (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Cashew leaves (Western cashew) contains compounds belonging to the class of flavonoids, tannins, and saponins which are thought to have antifungal activity against Candida albicans. This study aims to determine the antifungal activity of the ethanol extract of cashew leaves on growth Candida albicans based on the inhibition zone formed. The method for determining antifungal activity was carried out through disc diffusion. Cashew leaf extract was made into three different concentrations namely, 5%, 7.5%, and 10%, the negative control used 10% DMSO, and 2% ketoconazole as a positive control. Based on the results of the phytochemical screening, the ethanol extract of cashew leaves contains compounds belonging to the class of flavonoids, tannins and saponins. The results of the antifungal activity test of the ethanol extract of cashew leaves at concentrations of 5%, 7.5%, and 10% could inhibit the growth Candida albicans with the diameter of the inhibition zone respectively, 10.35 mm, 11.93 mm, 14.12 mm. The diameter of the inhibition zone on ketoconazole was 21.75 mm and no inhibition zone was formed in the negative control group. From the results of the study it was concluded that the ethanol extract of cashew leaves has activity against Candida albicans.